#TITLE_ALTERNATIVE# - (NIM : 10207098); Pembimbing : Dr. Inge M. Sutjahja; Dr. Daniel Kurnia , KHOERUDIN
Hall effect measurement is a standard measurement in physics of materials that can be used to determine the type, concentration and mobility of charge carriers are dominant in metals and semiconductors. To get the data value of the Hall voltage accurately take into account the effect of IR-drop caused by irregularities (misalignment) of the probe voltage, where the magnitude of the effect of IR-drop is proportional to the amount of misalignment. In this experiment we examined the effect of IR-drop-shaped aluminum foil material. In principle, a measurement tool setup consists of an electric current source, the magnetic field and the reader voltage (voltmeter). The maximum value of 3.1 kG magnetic field generated by an electromagnet of electric current and is also used as a switching transistor current source of electricity. Furthermore, the concentration of charge carriers generated Hall voltage data analysis will be compared with data references.